Association between CYP17A1 rs743572 polymorphism and cancer risk: A meta-analysis - Bin Wang; Zhumin Cao; Ying Li; Hua Zou (PLoS ONE, 2025)
The role of the CYP17A1 gene’s rs743572 polymorphism in cancer susceptibility has been a subject of extensive investigation, yet existing evidence remains inconclusive. In this meta-analysis, we systematically reviewed and synthesized data from 29 studies to assess the CYP17A1 rs743572 polymorphism’s relationship with cancer susceptibility. We strictly searched on EMBASE, PubMed, and Web of Science databases and explored rs743572 polymorphism’s association with cancer risks according to search strategy, enrolling 29 studies (13,767 cases and 17,441 controls). rs743572 was markedly related to enhanced cancer susceptibility risk; FPRP and TSA analyses were employed for confirmation. According to cancer type-based stratified analyses, rs743572 exhibited a notable association with bladder cancer, breast cancer, non-Hodgkin lymphoma, and hepatocellular cancer. In conclusion, systematic meta-analysis suggests a significant role for the rs743572 polymorphism in cancer pathogenesis, with particular prominence observed in bladder cancer, breast cancer, non-Hodgkin lymphoma, and hepatocellular cancer.